Piperlongumine inhibits diethylnitrosamine induced hepatocellular carcinoma in rats. (8th January 2022) - Kumar, Ashish; Naithani, Manisha; Kumar, Nitesh; Singh, Neha; Agrawal, Shruti; Sharma, Ambika; Thapliyal, Surabhi; Singh, Jagjit; Handu, Shailendra
Background: Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related death worldwide. Piperlongumine (PL) has been claimed to have cytotoxic and HCC inhibitory effects in various cancer cell lines and xenograft models, but the chemopreventive potential of PL has not been studied in experimentally induced HCC yet. Research Design: Twenty-four Wistar male rats were divided into four groups of six each, Group A: untreated control; Group B: Diethylnitrosamine (DEN) control (200 mg/kg), Group C: DEN + PL 10 mg/kg; and Group D: DEN + PL 20 mg/kg. Rats from all groups were assessed for liver cancer progression or inhibition by evaluating biochemical, cytokines, tumor markers, lipid peroxidation, and histological profiles. Results: The liver enzymes alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma-glutamyl transferase (GGT), alkaline phosphatase (ALP) levels, and lipid peroxidation were significantly decreased in Group C and Group D compared to Group B. Upregulation in the level of pro-inflammatory cytokines IL-1B, TNF-α, inflammatory mediator (NF-κB) and tumour marker alpha-fetoprotein (AFP) in Group B were brought down upon treatment with piperlongumine in a dose-dependent manner. Antitumor cytokine (IL-12) was upregulated in PL-treated rats compared to DEN control rats. DEN treated group (Group B) showed histological features of HCC, and in rats treated with PL (Groups C, D) partial to complete reversal to normal liver histoarchitecture was observed. Conclusions: The potential chemopreventive actions of piperlongumine may be due to its free radical scavenging and antiproliferative effect. Therefore, piperlongumine may serve as a novel therapeutic agent for the treatment of hepatocellular carcinoma.